Pengaruh Struktur Modal, Perputaran Modal Kerja, Firm Size, Dan Kebijakan Dividen Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2020-2022 - Juwita Dwi Maulidia Arisliani; Titiek Suwaarti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aimed to examine and analyze the influence of Capital Structure, Working Capital Turnover, Firm Size, and Dividend Policy on the Firm Value of Manufacturing Companies listed on the Indonesia Stock Exchange during the period 2020-2022. The method employed in this study was the Quantitative Method with the research sample obtained using the Purposive Sampling Technique, resulting in a total of 117 samples. The data analysis technique utilized in this research was multiple linear regression analysis. The results of this study indicate that Working Capital Turnover, Firm Size, and Dividend Policy have a positive impact on Firm Value, while Capital Structure does not have an impact on Firm Value. Keywords: Capital Structure, Working Capital Turnover, Firm Size, Dividend Policy, Firm Value